2007
DOI: 10.1084/jem.20071451
|View full text |Cite
|
Sign up to set email alerts
|

CD11cloB220+ interferon-producing killer dendritic cells are activated natural killer cells

Abstract: Interferon-producing killer dendritic cells (IKDCs) are a recently described subset of CD11cloB220+ cells that share phenotypic and functional properties of DCs and natural killer (NK) cells (Chan, C.W., E. Crafton, H.N. Fan, J. Flook, K. Yoshimura, M. Skarica, D. Brockstedt, T.W. Dubensky, M.F. Stins, L.L. Lanier, et al. 2006. Nat. Med. 12:207–213; Taieb, J., N. Chaput, C. Menard, L. Apetoh, E. Ullrich, M. Bonmort, M. Pequignot, N. Casares, M. Terme, C. Flament, et al. 2006. Nat. Med. 12:214–219). IKDC develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
145
3
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 28 publications
4
145
3
9
Order By: Relevance
“…6,7 However, several groups have recently questioned the existence of this cell subset as a separate lineage from NK cells, with the putative antigen presentation function of IKDC at the core of the controversy. [8][9][10] For some of these authors, IKDCs may represent an activated status of conventional NK cells. 8 IL-15 11,12 is an absolutely essential cytokine for the differentiation and maintenance of memory CD8 + T, NKT and NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, several groups have recently questioned the existence of this cell subset as a separate lineage from NK cells, with the putative antigen presentation function of IKDC at the core of the controversy. [8][9][10] For some of these authors, IKDCs may represent an activated status of conventional NK cells. 8 IL-15 11,12 is an absolutely essential cytokine for the differentiation and maintenance of memory CD8 + T, NKT and NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…These unconventional capabilities include [16,17,18] and direct pathogen recognition [19,20]. In this regard, a novel innate immune cell population called Interferon-producing killer dendritic cells has been recently described in mice [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These unconventional capabilities include [16,17,18] and direct pathogen recognition [19,20]. In this regard, a novel innate immune cell population called Interferon-producing killer dendritic cells has been recently described in mice [21,22].ICAM-1/CD54 is the major ligand of costimulatory a L b 2 integrin (CD11a/CD18), commonly known as lymphocyte function-associated antigen (LFA-1) [23,24]. The surface enhancement of ICAM-1 on endothelial, APC and B cells have pleiotropic effects in LFA-1-mediated T lymphocyte responses including T-cell homing [25], formation and stabilization of immunosynapse [26,27], T-cell memory differentiation [28], and Th1 polarization [29,30], among others.…”
mentioning
confidence: 99%
“…1,2 Other authors contend that these cells represent activated NK cells, as classical NK cells (cNK) (DX5 + CD3 À NK1.1 + B220 À ) acquire B220 on activation. [3][4][5] Recently, we reported that productive in vivo transfer of the IL-15 gene into the liver by hydrodynamic injection results in the proliferation and activation of both cNK cells and IKDC. 6 Furthermore, in the context of in vivo gene transfer of IL-15 into hepatocytes, 6 we made other observations centered on both the function and ontogeny of IKDC, which are relevant to this controversy.…”
mentioning
confidence: 99%
“…6 Furthermore, in the context of in vivo gene transfer of IL-15 into hepatocytes, 6 we made other observations centered on both the function and ontogeny of IKDC, which are relevant to this controversy. [1][2][3][4][5]7 DX5 + cells from the spleen of B6.SJL-Ptprc a Pep3 b / BoyJ mice (CD45.1 mice) were analyzed by fluorescence-activated cell sorting (FACS) analysis (to 98-99% purity) into DX5 + CD3 À NK1.1 + B220 À (cNK) and DX5 + CD3 À NK1.1 + B220 + (IKDC) fractions. Both populations once labeled by CFSE (carboxyfluorescein diacetate succinimidyl ester) were adoptively transferred into congenic C57BL/6J (CD45.2) mice, which had been hydrodynamically injected with the IL-15-encoding (pVKL/IL15IRESNeo) or control (pIRESNeo) plasmid 8 h before adoptive transfer, as detailed in Arina et al 6 Immunostaining of the CD45.1/CD45.2 polymorphism permitted unequivocal gating of the adoptively transferred cells.…”
mentioning
confidence: 99%